PENGARUH Biofertilizer DAN PUPUK NPK TERHADAP PERTUMBUHAN TINGGI TANAMAN TEMBAKAU (Nicotiana tabacum) - Sudiarti, Diah (JURNAL BIOSHELL, 2013)
consortia (Lactobacillus, Pseudomonas, Bacillus, Saccharomyces, Rhizobium, Azotobacter, Azospirillum, and Cellulomonas). The treatment consists of 4 biofertilizer concentrations (0, 5, 10, and 15 mL/plant) and 4 concentrations of NPK (0, 25, 50, and 75% is equivalent to 0; 1.25; 2.5; and 3.75 g NPK/plant), as well as the positive control (100% NPK equivalent 5g/plant). The result showed that treatment B2K2 (combination of biofertilizer 10 mL/plant and NPK 2.5 g/plant) and B3K2 (combination of biofertilizer 15 mL/plant and NPK 2.5 g/plant) gave better results compared with other treatments.Keywords: Biofertilizer, Nicotianae tabacum, NPK, Plant growth.